Full-Length 16S rRNA and ITS Gene Sequencing Revealed Rich Microbial Flora in Roots of Cycas spp. in China. (January 2021) - Pecundo, Melissa H; Chang, Aimee Caye G; Chen, Tao; dela Cruz, Thomas Edison E; Ren, Hai; Li, Nan
Cycads have developed a complex root system categorized either as normal or coralloid roots. Past literatures revealed that a great diversity of key microbes is associated with these roots. This recent study aims to comprehensively determine the diversity and community structure of bacteria and fungi associated with the roots of two Cycas spp. endemic to China, Cycas debaoensis Zhong & Chen and Cycas fairylakea D.Y. Wang using high-throughput amplicon sequencing of the full-length 16S rRNA (V1-V9 hypervariable) and short fragment ITS region. The total DNA from 12 root samples were extracted, amplified, sequenced, and analyzed. Resulting sequences were clustered into 61 bacteria and 2128 fungal OTUs. Analysis of community structure revealed that the coralloid roots were dominated mostly by the nitrogen-fixer Nostocaceae but also contain other non-diazotrophic bacteria. The sequencing of entire 16S rRNA gene identified four different strains of cyanobacteria under the heterocystous genera Nostoc and Desmonostoc . Meanwhile, the top bacterial families in normal roots were Xanthobacteraceae, Burkholderiaceae, and Bacillaceae. Moreover, a diverse fungal community was also found in the roots of cycads and the predominating families were Ophiocordycipitaceae, Nectriaceae, Bionectriaceae, and Trichocomaceae. Our results demonstrated that bacterial diversity in normal roots of C. fairylakea is higher in richness and abundance than C. debaoensis . On the other hand, a slight difference, albeit insignificant, was noted for the diversity of fungi among root types and host species as the number of shared taxa is relatively high (67%). Our results suggested that diverse microbes are present in roots of cycads which potentially interact together to support cycads survival. Our study provided additional knowledge on the microbial diversity and composition in cycads and thus expanding our current knowledge on cycad-microbe association. Our study also considered the possible impact of ex situ conservation on cyanobiont community of cycads.